Drum Brake Calculation on Daihatsu Xenia 1.3 F 601 - Pratama, Danis Agustian; -, Kardiman -; Naubnome, Viktor (TRAKSI, 2024)
The brake system is one of the components of the engine elements on the vehicle that can support the comfort and safety factor in driving. Brakes function to slow down or stop the movement of the wheels by means of friction. Brakes are a very important part of the car, good brake maintenance is very important because it involves the safety of the passengers. The brakes needed on a car are those that can work well and can be trusted, have sufficient braking power and besides that the brakes must be easy to adjust and check. The kinetic energy lost from moving objects is usually converted into heat due to friction. The purpose of this report is to find out the functions, working principles and calculations as well as to know the things that must be considered in planning the drum brake. The method used to make this report is from direct observation of objects, literature studies and measuring objects directly. From the drum brake specifications that have been described, we can find out the calculation steps needed to find the normal force on the rear wheel, the permissible frictional force on the asphalt, and the maximum force on the upper and lower springs. After several calculation steps, the results of the normal force on the rear wheel are 2873.9 N. The permissible frictional force on the asphalt is 712.17 N. The maximum force of the upper spring is 50.98 N, and the maximum force of the lower spring is 80. ,8 N